Effect of soy isoflavones on intraepithelial lymphocytes, goblet cells and long leptin receptor in intestinal of rats - TANG Xiuying; CHEN Zhengli; LUO Qihui; ZHANG Xiaolong (浙江大学学报. 农业与生命科学版)
Soy isoflavones (SIF) are a research focus due to their potential health effects. Some studies have shown that it could modulate immune function and prevention of chronic diseases, but until now it remains controversial. Thus, the aim of the present study is to investigate the effect of high-fat diet induced obesity on male immune parameters. Numerous studies have reported that immunomodulatory activity of intestinal mucosal barrier was related to intraepithelial lymphocytes (IEL) and goblet cells (GC). Leptin is secreted almost exclusively by adipocytes. Previous researches demonstrated that plasma leptin levels in ovariectomized rats was lower than that in estradiol-treated animals. Moreover, there was a tissue-specific regulation of the leptin receptor (OB-Rb), with less sensitivity to leptin in adipose tissue when the time of treatment or the dose of estradiol administered increased. The metabolites of soy isoflavones showed structural and functional similarities to estradiol. Available data indicated that soy isoflavones inhibited the leptin secretion, and thus influenced the expression of OB-Rb.The study was divided into two steps. In the first experiment, male Sprague-Dawley rats were fed with a high sugar and fat diet (HSF) or basal diet for eight weeks. Food intake and animal mass were recorded weekly. In the second experiment, 40 selected obese rats were randomly divided into four groups with 10 rats in each group and were fed with soy isoflavones (group Ⅰ 0 mg/kg, group Ⅱ 50 mg/kg, group Ⅲ 150 mg/kg and group Ⅳ 450 mg/kg) and 10 control rats (group V) were fed with basal diet for four weeks. Soy isoflavones was gavaged with 0.5% sodium carboxymethyl cellulose solutions respectively. At the end of the second experiment, rats were slightly anesthetized with sodium pentobarbital ip (40 mg/kg), and intestinal was taken and fixed in 10% neutral buffered formalin, processed and trimmed, embedded in paraffin. IEL and GC in the villus epithelium were evaluated in these rats, as well as the OB-Rb expression by immunohistochemistry staining.In the first experiment, the body mass of the HSF-fed animals were significantly increased after eight weeks and the obesity module was succeeded. In the second experiment, the results showed that the structure of mucous epithelium, intraepithelial lymphocyte and the goblet cells were normal in the intestinal. The intraepithelial lymphocytes of rats were mainly small lymphocytes and located around the epithelial basement membrane. Goblet cells distributed in the intestinal mucous epithelial lamina, and OB-Rb positive cells distributed in the intestinal mucous epithelial lamina and lamina propria, respectively. Compared with 0 mg/kg-SIF group, there was a tendency that IEL in the villus epithelium moved inward intestinal entoderm in SIF-treated rats. Quantitative analysis of IEL and GC in the villus epithelium showed the number of GC in duodenum, jejunum, ileum, colon had a increasing tendency from the forepart to the back of intestinal. The number of IEL and GC in the epithelium in the 450 mg/kg-SIF group were increased significantly (P<0.05), and there was significant difference in numbers of GC between the control and other groups. The changes of OB-Rb were relatively irregular in each part of the intestinal. The OB-Rb expression also increased significantly (P<0.05) in intestinal mucous membrane in the 450 mg/kg-SIF group.IEL and GC may play a very important role in the local mucosa immunity. The low number of IEL and GC showed that obesity may impair the immune function of rats. The results showed that SIF can affect mucosal immunity by increasing the number of IEL and GC. The OB-Rb expression of SIF-treated rats was significantly increased compared with untreated ones. We deduced that SIF contains a number of biologically active components with potential immunomodulatory activity, and SIF could modulate intestinal mucosal immunity of rats.